Manifestation of coronary subclavian steal phenomenon using reactive hyperemia in the ipsilateral forearm. Issue 10 (1st October 2019) - Iino, Takako; Yamanaka, Takayuki; Sato, Wakana; Iino, Kenji; Watanabe, Hiroyuki
Abstract: Coronary subclavian steal syndrome (CSSS) is a coronary steal phenomenon secondary to subclavian artery stenosis in patients who have undergone coronary bypass surgery with the internal thoracic artery. Most commonly, CSSS is diagnosed angiographically. Our case emphasizes that stress ultrasound assessment using reactive hyperemia in the ipsilateral arm elicits a functional diagnosis of CSSS.